PENDAPATAN ASLI DAERAH: APAKAH PAJAK DAERAH BERKONTRIBUSI? - Putri, Yuan Laterina; Nuraini A, Nuraini A (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
Local taxes are one of the important components in the receipt of Regional Original Income (PAD). However, the phenomenon of tax arrears still occurs in several districts/cities in Aceh Province, which will certainly have an impact on PAD revenue. This study aims to determine how much effectiveness the collection of Hotel Tax, Restaurant Tax and Land and Building Tax (PBB) is and their contribution to local revenue in the Regency/City Government in Aceh Province. The population in this study were 22 District/City Governments in Aceh Province. This type of research is descriptive quantitative research. The data used is secondary data in the form of data on the realization of the Regional/City Revenue and Expenditure Budget Realization Reports throughout the Aceh Province for 2017-2019. The data was obtained from the Aceh Financial Management Agency (BPKA). The results showed that the level of effectiveness of hotel taxes in districts/cities in Aceh Province for the 2017-2019 period was classified as less effective with an average percentage of 78.59%. The level of effectiveness of restaurant taxes in districts/cities in Aceh Province for the 2017-2019 period is classified as effective with an average percentage of 92.94% while the effectiveness level of PBB P2 is still classified as less effective with an average percentage of 65.64%. The contribution level of Hotel Tax, Restaurant Tax and PBB P2 collection to Regional Original Income in districts/cities in Aceh Province for the 2017-2019 period is classified as very poor with an average percentage of 1.08%, 1.50% and 0,36%.